uso de apps para dinamizar la enseñanza y el aprendizaje de la asignatura lengua y literatura en los estudiantes de quinto de egb en la unidad educativa particular católica “virgen de fátima” - Ramirez Calderon, Karla Cecilia; Guaman Rogel, Roger Alexis (Machala, 2025)
The objective of this study is to evaluate the impact of the implementation of a gamified educational application in the dynamic and participatory learning of students in the 5th year of General Basic Education, in the subject of Language and Literature, in the private school “Virgen de Fátima”. Through observations made in the classroom, it became evident that traditional teaching methods did not favor dynamic learning or motivate the interaction of students with the contents, for this reason, it was proposed to explore how the use of Information and Communication Technologies can improve the active participation of students and their academic performance through the development of an interactive tool that facilitates teaching and learning. To achieve this objective, the Divert Track mobile application was designed based on the ADDIE model, a systematic approach that guided its creation and evaluation. The research was developed under a mixed methodology, combining quantitative and qualitative approaches. The quantitative approach allowed for the collection of numerical data through pre- and post-test surveys, while the qualitative approach facilitated an in-depth understanding of student behaviors and needs through observations and interviews. In the first phase of the experience, the application was presented to the subject teacher, who was an integral part of the design process. She relied on the didactic unit plan to develop the resources and activities within the application. After an initial introduction and navigation of the app, her feedback was gathered through an interview. The teacher indicated that the activities within the app met her expectations, highlighting its potential to make learning more dynamic and engaging. However, she suggested the incorporation of a final assessment that would allow students to test the knowledge acquired throughout the topics studied. This feedback was key to make adjustments and improve the tool before applying it to the students. In the second phase, the application was implemented with the students through a demonstration class using the app. A pre-test survey was conducted to measure their initial reading comprehension level, and a post-test survey was conducted after the use of the app, to evaluate the impact on their academic performance and active participation in class. During this phase, a notable change was observed in the students' attitude towards reading, showing greater interest and participation, especially during the interactive activities. The results obtained in the tests evidenced a significant improvement in the students' reading comprehension, which was confirmed through statistical analysis using the SPSS program. In conclusion, the implementation of the gamified educational application “Divert Track” had a positive impact on students' learning, improving their reading comprehension and their participation in the teaching-learning process. The tool proved to be effective as an educational strategy, promoting an innovative and attractive way of teaching, aligning with the needs and expectations of teachers and students.
El presente estudio tiene como objetivo evaluar el impacto de la implementación de una aplicación educativa gamificada en el aprendizaje dinámico y participativo de los estudiantes de 5to año de Educación General Básica, en la asignatura de Lengua y Literatura, en la escuela particular “Virgen de Fátima”. A través de observaciones realizadas en el aula, se evidenció que los métodos tradicionales de enseñanza no favorecían un aprendizaje dinámico ni motivaban la interacción de los estudiantes con los contenidos, por esta razón, se planteó como propósito explorar cómo el uso de Tecnologías de la Información y Comunicación puede mejorar la participación activa de los estudiantes y su rendimiento académico mediante el desarrollo de una herramienta interactiva que facilite la enseñanza y aprendizaje. Para alcanzar este objetivo, se ha diseñado la aplicación móvil Divert Track basándose en el modelo ADDIE, un enfoque sistemático que guió su creación y evaluación. La investigación se desarrolló bajo una metodología mixta, que combina enfoques cuantitativos y cualitativos. El enfoque cuantitativo permitió la recolección de datos numéricos a través de encuestas pre y post test, mientras que el enfoque cualitativo facilitó la comprensión profunda de los comportamientos y necesidades de los estudiantes mediante observaciones y entrevistas. En la primera fase de la experiencia, se presentó la aplicación a la docente de la asignatura, quien fue parte integral del proceso de diseño. Se basó en el plan de unidad didáctica para desarrollar los recursos y actividades dentro de la aplicación. Tras una introducción y navegación inicial de la app, se recopiló su opinión mediante una entrevista. La docente indicó que las actividades dentro de la aplicación cumplían con sus expectativas, destacando su potencial para hacer el aprendizaje más dinámico y atractivo. No obstante, sugirió la incorporación de una evaluación final que permitiera a los estudiantes poner a prueba los conocimientos adquiridos a lo largo de los temas estudiados. Esta retroalimentación fue clave para realizar ajustes y mejorar la herramienta antes de aplicársela a los estudiantes. En la segunda fase, se implementó la aplicación con los estudiantes, mediante una clase demostrativa utilizando la app. Se realizó una encuesta pre-test para medir su nivel de comprensión lectora inicial, y una encuesta post-test tras el uso de la aplicación, para evaluar el impacto en su rendimiento académico y en la participación activa en clase. Durante esta fase, se observó un notable cambio en la actitud de los estudiantes hacia la lectura, mostrando mayor interés y participación, especialmente durante las actividades interactivas. Los resultados obtenidos en los tests evidenciaron una mejora significativa en la comprensión lectora de los estudiantes, lo que fue confirmado a través de un análisis estadístico utilizando el programa SPSS. En conclusión, la implementación de la aplicación educativa gamificada “Divert Track” tuvo un impacto positivo en el aprendizaje de los estudiantes, mejorando su comprensión lectora y su participación en el proceso de enseñanza-aprendizaje. La herramienta demostró ser efectiva como estrategia educativa, promoviendo una forma innovadora y atractiva de enseñar, alineándose con las necesidades y expectativas de docentes y estudiantes.
Keywords: GAMIFICACION; INTERACTIVA; APLICACION MOVIL